Low-energy experiments at the S3 spectromet - S., Franchoo (Nuclear Science and Technology, 2019)
With the advent of the Spiral-2 linear accelerator and the associated S3 spectrometer at the Ganil laboratory in France, new realms of intermediate-mass N=Z and very heavy nuclei will soon become available for research in nuclear structure. After their production and selection in the spectrometer, the ions of interest will be stopped in a buffer gas, neutralised, resonantly re-ionised, cooled and bunched. This will bring us in an adequate position to perform laser spectroscopy, mass measurements and decay spectroscopy of their ground and isomeric states. In this contribution we report on the ongoing commissioning of the detector set-up.